Affective communication during bad news consultation. Effect on analogue patients' heart rate variability and recall. Issue 11 (November 2018) - Danzi, Olivia Purnima; Perlini, Cinzia; Tedeschi, Federico; Nardelli, Mimma; Greco, Alberto; Scilingo, Enzo Pasquale; Valenza, Gaetano; Del Piccolo, Lidia
Highlights: Few supportive comments improve patient's perception of empathy and support. Supportive communication can help to reduce the patient's level of arousal. Supportive communication is not sufficient to improve recall of provided information. Abstract: Objective: The aim of the study was to investigate the effect of physicians' supportive communication on analogue patients' (APs) heart rate variability (HRV) and recall, while watching a video of palliative treatment being explained to a female patient. Methods: Sixty healthy women, acting as APs, were randomly assigned to watch one of two versions (standard vs. affective) of a scripted video-vignette of a bad news consultation to a female patient. The physician's communication differed only in the delivery of four supportive comments. Empathy, support and engagement perception were assessed by three questions. APs' HR was recorded during video-observation and recall was assessed immediately after. HRV was determined through measures defined in time and frequency domains. Results: Data of 54 APs (27 + 27) were included. The group with supportive communication perceived the physician as more empathic and supportive. Intra- and Inter-group comparisons suggested a greater sense of stress in the standard communication group. Recall did not differ in the two groups. Conclusion and practice implications: Findings show that the use of supportive expressions contribute to the perception of the physician as more empathic, potentially buffer patients' arousal after a bad news announcement, but does not confirm a positive impact on general recall.